How evolving gender norms and social change impact rural farming villages - GENNOVATE (International Maize and Wheat Improvement Center, 2018)
The GENNOVATE video raises awareness about and explores the interlinkages between gender norms, agency, and innovation in agriculture and natural resource management from the perspectives of local women and men themselves. It includes stories of men and women from Tanzania, Nepal, and Mexico. By actively involving women and men farmers as first person narrators who articulate their experiences and perspectives in their own words, the videos complement GENNOVATE's other research products and reify the project's core concerns of voice, agency, and empowerment